Crusted Scabies dengan Infeksi Sekunder pada Lupus Eritematosus Sistemik Berat : Laporan Kasus - Sabana, Manusama Hasan; Sumadiono; Satria, Cahya Dewi (Jurnal Kebidanan dan Kesehatan, 2024)
Background: Crusted scabies is characterised by hyperkeratosis and crusting of the skin due to profuse proliferation of S. scabiei mites. Clinical manifestations arise due to altered host response to mite infestation, such as in systemic lupus erythematosus (SLE) patients with immunocompromised conditions. This study aims to review clinical data: This study is a case report relating to cases found in 2020. Case illustration: In this case, a 17-year-old girl was diagnosed with SLE nephritis since September 2020. The patient was treated with severe SLE protocol, namely high dose methylprednisolone followed by full dose orally and Mycophenolate Mofetil (MMF). The patient presented with complaints of a reddish rash with scabs on the face. Examination of skin abnormalities in the malar region found erosions covered with multiple scattered red-black crusts with a base of erythema patches, skin scrapings between fingers found mite bodies and eggs. Laboratory results showed anaemia, hyperuricaemia, elevated anti dsDNA, strong positive ANA IF. Urinalysis found proteinuria and glucosuria. Permethrin 1% was given once per week until clinical improvement. Cefepime antibiotic was given to treat secondary infection of scabies. The severe SLE protocol was continued. Conclusion: Severe manifestations of scabies infection in SLE patients are associated with immunocompromised conditions as well as immunosuppressive drug administration. Adequate scabies therapy and antibiotics for secondary infections are needed to prevent morbidity in patients with SLE.